The spatial variation of the displaced population in Wasit Governorate - هاشم كزار الطائي لطيف; جعفر عزيز الطائي براء (Journal of College of Education, 2019)
The research is concerned with the study of population displacement, which is a geographical phenomenon that has not been studied or delve into at the level of Wasit province in its administrative units. The study dealt with the numerical and population distribution of the displaced population in the administrative units of Wasit Governorate and for the years (2005, 2007, 2015 and 2017), which is one of the important topics that the geographical researchers are looking for in order to know The number of displaced persons in each administrative unit with the extent of variation in the distribution of the displaced within the study area of different years studied. The research found that the displaced population varied in distribution between the administrative units and for many years significantly, due to the different size and direction of the waves of displacement both in space and time .